EKSPLORASI KEMAMPUAN BERORGANISASI SANTRI MELALUI KEPEMIMPINAN TRANSFORMASIONAL PEREMPUAN - Rofiki, Moh; Shoimah, Nur Khamidatus; Diana, Eka (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2023)
This research aims to analyze the methods used by women's transformational leadership in improving the organizational abilities of students in the Az-Zainiyah area of ​​the Nurul Jadid Paiton Probolinggo Islamic boarding school. This research explores the impact of women's transformational leadership roles on santri's organizational abilities, emphasizing the relevance of these skills in the context of inclusive and sustainable Islamic education. The qualitative approach used in this research is a case study type. The selection of objects in the Az-Zainiyah region was based on considerations because they have produced many successful alumni who are involved in government organizations. The techniques used to collect research data consist of in-depth interviews, participant observation, and documentation. Where the research data consists of primary data obtained from several research informants, namely the regional head, three Az-Zainiyah regional administrators, five Az-Zainiyah students and five Az-Zainiyah alumni. Meanwhile, secondary data was obtained from national and international journals that were relevant to research. The data analysis techniques used consist of data reduction, data display, and drawing conclusions. The research results show that women's leadership methods in improving santri organizations are carried out by providing santri organizations, holding training and competency development, providing practical experience through various activities, and providing facilities. Women's transformational leadership has a significant impact on improving student organization